WOCE radiocarbon IV: Pacific Ocean results; P10, P13N, P14C, P18, P19 & S4P - Key, R. M.; Quay, P. D.; Schlosser, P.; McNichol, A. P.; von Reden, K. F.; Schneider, R. J.; Elder, K. L.; Stuiver, M.; Ostlund, H. G. (Radiocarbon, 2002)
The World Ocean Circulation Experiment, carried out between 1990 and 1997, provided the most comprehensive oceanic survey of radiocarbon to date. Approximately 10,000 samples were collected in the Pacific Ocean by U.S. investigators for both conventional large volume P counting and small volume accelerator mass spectrometry analysis techniques. Results from six cruises are presented. The data quality is as good or better than previous large-scale surveys. The C-14 distribution for the entire WOCE Pacific data set is graphically described using mean vertical profiles and sections, and property-property plots.
591keTimes Cited:33Cited References Count:56